PENGARUH KUALITAS PELAYANAN ADMINISTRASI TERHADAP KEPUASAN LAYANAN DI KANTOR DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN KUBU RAYA - RAHMANIAR1, ADE DWINANDA; Kusnadi, Dedi; Aprianto, Dhidik (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
The writing of this research aimed to determine the effect of the quality of administrative services on service satisfaction at the Kubu Raya Regency Education and Culture Office. The office naturally must have a decent level of service quality. The formation and development of satisfaction itself are supported by many factors, one of which is the service quality of the company and its employees. This research used the theory of Hassel Nogi S (2005:208) by using two variables, namely service quality and service satisfaction. The research type was associative research with quantitative approach and a total population of 2160 people. By using the Slovin formula and an error rate of 10%, a sample of 96 people was obtained. This research used closed questionnaire, and google form as a medium for distributing questionnaires and the SPSS version 23.0 program as a media for data analysis. Based on the results of calculations using the T test, the results obtained a significance of 0.000. The number was smaller than the probability of 0.05. Thus, it was concluded that there was a significant effect between service quality and service satisfaction.Keywords: Effect, Service Quality, Service Satisfaction.